2010
DOI: 10.1017/s014271641000007x
|View full text |Cite
|
Sign up to set email alerts
|

What compound words mean to children with specific language impairment

Abstract: Sixteen children (17 age mates, 17 vocabulary mates) with specific language impairment (SLI) participated in two studies. In the first, they named fantasy objects. All groups coined novel noun–noun compounds on a majority of trials but only the SLI group had difficulty ordering the nouns as dictated by semantic context. In the second study, the children described the meaning of conventional noun–noun compounds. The SLI and AM groups did not differ in parsing the nouns, but the SLI group was poorer at explainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Sheng and McGregor (2010) found a range of abilities in lexical-semantic organization for 7-year-old children with SLI, and identified a subgroup with significant impairment in this skill set that was associated with word-finding deficits. McGregor, Rost, Guo and Sheng (2010) found semantic deficits in school-aged children with SLI in terms of their ability to use appropriate, semantically-dictated word order and explain the meaning of novel compound words. McGregor, Newman, Reilly and Capone (2002) have also found that naming errors were associated with less richly encoded semantic information.…”
Section: Introductionmentioning
confidence: 91%
“…Sheng and McGregor (2010) found a range of abilities in lexical-semantic organization for 7-year-old children with SLI, and identified a subgroup with significant impairment in this skill set that was associated with word-finding deficits. McGregor, Rost, Guo and Sheng (2010) found semantic deficits in school-aged children with SLI in terms of their ability to use appropriate, semantically-dictated word order and explain the meaning of novel compound words. McGregor, Newman, Reilly and Capone (2002) have also found that naming errors were associated with less richly encoded semantic information.…”
Section: Introductionmentioning
confidence: 91%
“…Although lexical deficits in some children with ASD and SLI have been identified, only a few previous studies explored the underlying semantic organization in children with ASD and SLI (Battaglia, 2013; McGregor et al, 2012; McGregor, Rost, Guo, & Sheng, 2010). For example, McGregor and colleagues (2010) investigated how children organize and relate words to one another.…”
Section: Introductionmentioning
confidence: 99%
“…For example, McGregor and colleagues (2010) investigated how children organize and relate words to one another. They examined whether children understood the semantic relationship between the modifier and the head in compound words by asking children to make up compound names to describe pictures; children were also asked to parse and explain compound words.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological-awareness deficits have indeed been linked with SLI in English (Oetting & Rice, 1993;Smith-Lock, 1995;Van der Lely & Christian, 2000). On morphological construction tasks similar to that used in Cantonese Chinese (constructing novel word compounds such as ghost-camel), English-speaking children with SLI performed significantly worse than their controls, particularly in the correct ordering of the root noun and modifier (Grela, Synder, & Hiramatsu, 2005;McGregor, Rost, Guo, & Sheng, 2010). In Cantonese Chinese, children with co-morbid SLI-D or SLI-only also perform worse than those with normal language on morphological construction (Wong et al, 2010).…”
Section: Morphological Awarenessmentioning
confidence: 99%